2022
DOI: 10.1007/s00405-022-07781-1
|View full text |Cite
|
Sign up to set email alerts
|

Parosmia as a predictor of a better olfactory function in COVID-19: a multicentric longitudinal study for upper respiratory tract infections

Abstract: Purpose This study aimed to evaluate the course of olfactory dysfunction [OD] due to upper respiratory tract infections [URTI] especially for COVID-19 [C19] in a multicentric design and to investigate possible predictors for the outcome. Methods In a multicentric study, patients (n = 147, of which 96 were women) with OD due to URTI, including C19 and non-C19 were evaluated at two visits with a standardized medical history and “Sniffin’ Sticks” extended psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
2
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
1
6
2
3
Order By: Relevance
“…Four out of five patients complained of parosmia, in line with other studies 34 , 60 . These reports are consistent with the theory that parosmia is believed to be a part of the recovery process in patients with impaired olfactory function 61 , 62 . All patients reported the distorted smell and taste to be of an unappealing character.…”
Section: Discussionsupporting
confidence: 91%
“…Four out of five patients complained of parosmia, in line with other studies 34 , 60 . These reports are consistent with the theory that parosmia is believed to be a part of the recovery process in patients with impaired olfactory function 61 , 62 . All patients reported the distorted smell and taste to be of an unappealing character.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, in contrast with previous authors [11][12][13][14]39 we did not find any effect of age on smell recovery. On the other hand, we found a positive significant effect of presence of comorbidities on discrimination scores ( p = .048) which in some aspects corroborates previous results from Chudzik et al 11 who concluded that the risk of developing long-COVID smell loss is greater in people with less comorbidities.…”
Section: Discussioncontrasting
confidence: 99%
“…In another survey on 798 participants Coelho et al 12 showed that age <40 and presence of nasal congestion at time of COVID‐19 infection were predictive of improved rates of smell recovery, while difficulty breathing at time of COVID‐19 infection, and prior head trauma predicted worsened rates of recovery. A positive influence of age (age < 40) on smell recovery was also confirmed by McWilliams et al 13 In a multicentric study on 147 patients, Menzel et al 14 using Sniffin' Sticks (S'S) observed a better prognosis in younger patients with parosmia and lower olfactory scores at the first visit. Conversely, Schwab et al 15 found that parosmia, high severity of OD, and female sex were associated with lower rates of recovery.…”
Section: Introductionmentioning
confidence: 71%
“…Das häufige unangenehme Begleitsymptom einer Parosmie als qualitative Riechstörung wird schon seit Längerem auch als gutes Zeichen einer sich vollziehenden Heilung postviraler quantitativer Riechstörungen diskutiert [11,12]. Jetzt mehren sich die Hinweise, dass das auch auf die Prognose von C19-assoziierten olfaktorischen Funktionsstörungen zutrifft [13,14]…”
Section: Introductionunclassified
“…Das häufige unangenehme Begleitsymptom einer Parosmie als qualitative Riechstörung wird schon seit Längerem auch als gutes Zeichen einer sich vollziehenden Heilung postviraler quantitativer Riechstörungen diskutiert [11,12]. Jetzt mehren sich die Hinweise, dass das auch auf die Prognose von C19-assoziierten olfaktorischen Funktionsstörungen zutrifft [13,14] Aus einer alters-und geschlechtsbezogenen Normwerttabelle [16] ließen sich 3 quantitative Riech-Diagnosen (RD) bestimmen: 1. Ein alters-und geschlechtsbezogen normales Riechvermögen (RDn) lag vor, wenn der SDI zwischen der 95. und einschließlich der 10.…”
Section: Introductionunclassified